Biology in a social context: a comprehensive analysis of humanization in introductory biology textbooks - Meuler, Madison; Lee, Jiae; Foutch, Katherine; Al-Khayat, Noor; Boukouzis, Katerina; Christensen, Priya; Crooks, Carmella; Hassanain, Lubna M.; Karimi, Parnian; Kim, Galina V.; Randall, Alyssa; Redford, Ingrid K.; et al. (Frontiers in Education, 2023)
To grapple with the sterility and Whiteness of Western science, scholars have proposed a pedagogical shift to culturally relevant and/or culturally sustaining pedagogy. A key tenet of culturally relevant pedagogy is a focus on developing students' ability to use the knowledge they obtain to identify, analyze, and solve real-world problems. Thus, the ability to foster this consciousness amongst students and make justice/injustice visible within biology curricula is an act of humanization. Here, we characterize and quantify the extent to which six prominent introductory biology US-based textbooks include humanizing content. First, we built consensus on what it means to humanize biology in a textbook by iteratively revising a coding protocol until we achieved a continuum of humanization. Our continuum evaluates the quantity, location, and the nature of the humanizing element within the textbook. Then, we used the continuum to collect data through qualitative coding: each chapter of each textbook was coded by two coders who came to consensus on the humanizing elements within. We find that in general, the inclusion of humanizing content in introductory biology textbooks is rare: of the 9,670 pages of textbooks that we analyzed, we found 1352 humanizing passages but the vast majority of these were discussed in a single sentence (23%) or multiple sentences (61%), rarely multiple paragraphs (13%) or entire sections (2%). Similarly, of the 9,262 questions in the books (e.g., in section or chapter summaries), only 2.5% of them were humanizing and of those, only (64%) provided an answer, and of the ones that provided an answer, we only coded 42% of the answers as humanizing. In addition to quantifying the amount of humanization, we also describe the ways in which the passages were presented. For example, only about 9% of the humanizing passages included nuance, 5% discussed equity/inequity, and only 4% positioned biology as a means to accomplish justice. In all, we present what we believe is the most comprehensive assessment of humanizing elements in introductory biology textbooks and pair that with specific guidance to instructors who seek to include humanizing elements in their classes.